Pharmacokinetic properties of the preparations of protein origin - A. A. Soldatov; Zh. I. Avdeeva; N. A. Alpatova; N. V. Medunitsyn; S. L. Lysikova; V. A. Merkulov (Биопрепараты: Профилактика, диагностика, лечение, 2018)
Biological preparations differ substantially from low molecular weight chemicals in molecular weight, multidimensional structure of an active substance, presence of post-translational modifications, composition of impurities and excipients, drug manufacturing process, etc. These specific features of biological preparations also influence their pharmacokinetic properties. The assessment of pharmacokinetic properties is essential not only for the confirmation of the efficacy of a biological preparation, but it is also key aspect of demonstrating the similarity/analogy of a biosimilar preparation under development and the reference (original) preparation. High molecular weight biological preparations when administered subcutaneously and intramusculary initially migrate from the injection site into lymphatic vessels and then to blood. Pharmacokinetic properties of drugs with Fc region of immunoglobulin, are affected by their ability to interact with Fcy and FcRn receptors. Almost all biological preparations possess immunogenicity, the appearance of antibodies to a drug causes changes not only in pharmacodynamic but also in pharmacokinetic properties of biological products. The assessment of pharmacokinetic properties is a complicated and time-consuming process, for example, the study of drug distribution may in some cases require the use of a radioactive label.